The Genetics of Dementia with Lewy Bodies: Current Understanding and Future Directions - Orme, Tatiana (Curr Neurol Neurosci Rep, 2018)
PURPOSE OF REVIEW: Dementia with Lewy bodies (DLB) is a neurodegenerative disease that can be clinically and pathologically similar to Parkinson’s disease (PD) and Alzheimer’s disease (AD). Current understanding of DLB genetics is insufficient and has been limited by sample size and difficulty in diagnosis. The first genome-wide association study (GWAS) in DLB was performed in 2017; a time at which the post-GWAS era has been reached in many diseases. RECENT FINDINGS: DLB shares risk loci with AD, in the APOE E4 allele, and with PD, in variation at GBA and SNCA. Interestingly, the GWAS suggested that DLB may also have genetic risk factors that are distinct from those in AD and PD. SUMMARY: Although off to a slow start, recent studies have reinvigorated the field of DLB genetics and these results enable us to start to have a more complete understanding of the genetic architecture of this disease.